Recepcja obrazowanych wartości – próba analizy i wniosków badawczych - Cich, Bernadeta (Kultura Media Teologia, 2025)
In contemporary visual culture, saturated with persuasive and ocularcentric messages, the image functions as a relevant code for constructing communications that manifest values. The aim of this article is to analyze the reception of visualized values – specifically, how audiences respond to visual valor, how they interpret it, what linguistic means they use, which personal experiences they reference, and what mental images they associate with core personalist values. The analysis considers both emotional responses and the linguistic–visual strategies used to articulate values. The article is empirical in nature and continues previous research on the rhetorical visualization of values in graphic and cinematic social media discourse. Three methodological approaches were applied, corresponding to three types of empirical studies: Experimental research examining the effects of exposure to visual valor through EEG measurement using the EMOTIV device; Linguistic–semiotic screening research analyzing user interactivity through language and coding of comments posted in response to selected visual valor materials; Experimental research combined with linguistic, semiotic, and visual analysis conducted on a targeted research sample.